Double jeopardy [videorecording (DVD)] - Jones, Tommy Lee, 1946-; Judd, Ashley (Paramount Home Entertainment, 2010)
A woman, framed for the murder of her husband, emerges from a ten year prison sentence determined to find her son and the real murderer. Only her beaten down parole officer stands in her way.